Heavy Metals Contamination in Water and Aquatic Plants in the Tha Chin River, Thailand - Veschasit, Oning; Meksumpun, Shettapong; Meksumpun, Charumas (Agriculture and Natural Resources, 2012)
Evaluation of the distribution of heavy metals (cadmium: Cd, lead: Pb, copper: Cu and zinc: Zn) in water and two varieties of aquatic plants in the Tha Chin River, Samut Sakhon, Thailand, was performed in March and November, 2006. The results ranged from ND (not detected) to 0.05, ND to 1.04, 0.01 to 1.20 and 0.16 to 7.47 mg.L-1 for Cd, Pb, Cu and Zn, respectively. Although most of these heavy metals were within the range of standard values, some stations were higher than standard for lead and copper. The highest contamination of these heavy metals was found at stations near the river mouth during the wet season. Concentrations of Cd, Pb, Cu and Zn in Ipomoea aquatica ranged from ND to 0.22, ND to 2.42, 0.69 to 8.42 and 18.83 to 94.09 mg per kilogram dry weight, respectively. Results for Neptunia oleracea ranged from ND to 0.30, ND to 1.50, 2.00 to 13.13 and 16.33 to 78.70 mg per kilogram dry weight, respectively. The concentration of zinc in water, as well as lead in I. aquatica, showed signiﬁ cant seasonal differences (P < 0.05). Analysis revealed that copper in I. aquatica positively correlated with copper in water, indicating a potential use of these plants for pollution monitoring. Both I. aquatica and N. oleracea offer potential for bio-remediation, reducing the heavy metal pollution of the water body in which these plants are grown.